REVIEW OF PT SHARK SURYA DISTRIBUTION'S PETTY CASH ACCOUNTING SYSTEM AND SPENDING - Kadir, Risnawati; Pratiwi, Yana Eka; Lastiani, Siwidyah Desi (Universitas 17 Agustus 1945 Surabaya, 2024)
Petty Cash is very important to the company's operating activities. Usually used in small nominal transactions that occur every day from the start of the company's operating hours to the end of operating hours. The purpose of this study was to identify the Petty Cash Fund Recording System and the Use of Petty Cash Funds by PT. Shark Surya Distribution. Data collection methods include documentation, interviews, and observation sheets. Descriptive analysis is a data analysis technique. This research found that PT. Shark Surya Distribution uses the Imprest fund system, which records when the initial balance is topped up and when it must be replenished by a small cash fund recording system, as a small shoot fund recording system. Using small cash at PT. Shark Surya Distribution is generally correct; it is simply that certain monies are spent without discrimination and are not recorded in the petty cash financial records information system. The authors suggest that all areas of financial recording and reporting are governed by Required Standard Operating Procedures (SOPs). This SOP should include specific recommendations for tracking petty cash finances as well as strategies for dealing with any discrepancies that may develop.